The Study Of English Literature - Maharsi, Ista (Journal of English and Education (JEE), 2012)
Learning English language and English literature seems to bring about considerable questions of the benefits and the importance of so doing. Why should students who learn English language require learning English literature at the same time? The ultimate matter remains the samewhat is the very core of learning the subject? What do their relationships embrace? What, why, and how are we supposed to know that?Keywords: English language, English literature